Geotecnologias e atributos dos solos para análise ambiental de unidade de conservação no semiárido - Viana, Noely Silva (2024)
When discussing the Brazilian Semi-Arid region, concerns arise due to its unique characteristics associated with degrading human activities such as inadequate agricultural practices, burning, and deforestation. Addressing the issues of degradation and the urgent need for protection and recovery, the implementation and proper management of conservation units (UCs) are shown to be important strategies. An example is the Private Natural Heritage Reserve (RPPN) Fazenda Não Me Deixes, located in the municipality of Quixadá, Ceará. The objectives of this work were to physicochemically characterize three areas with different uses and occupations within the RPPN and the farm, namely: native forest (MN), degraded area in regeneration (AR), and agriculture (AG). Additionally, it aimed to identify land use and occupation through geotechnologies to observe the long-term effects of the UC. Throughout the research, field visits were conducted in the study areas to collect soil samples and location points. Analyses of soil density, textural classification, total organic carbon, total nitrogen, pH, electrical conductivity, phosphorus, sodium, potassium, calcium, magnesium, potential acidity, and aluminum were performed. Besides laboratory processes, geotechnologies such as NDVI and supervised classification were executed, both using QGIS software version 3.16.16. Upon completion of laboratory analyses, statistical techniques were applied, including Principal Component Analysis (PCA), Canonical Discriminant Function Analysis (CDFA), Multivariate Analysis of Variance (MANOVA), and Tukey's test in the free version of SAS® software. CDFA demonstrated that the areas are grouped based on chemical attributes. MANOVA rejected the null hypothesis that all areas have the same mean vector, and Tukey's test confirmed that AG statistically differs from MN and AR, but MN and AR do not differ from each other. NDVI corroborated changes in the RPPN area over the years since its creation, with a reduction in exposed soil areas and the emergence of semi-open shrub vegetation class. Supervised classification resulted in five classes: cloud, water, dense vegetation, sparse vegetation, and exposed soil.